The Ontogenesis of Social Representation of Justice: Personal Conceptualization and Social Constraints - Barreiro, Alicia Viviana (2013)
This paper analyzes the relations between the ontogenesis of social representations (SR) of justice and the individual?s conceptualization activity. A study was carried out with 216 children and adolescents from Buenos Aires Argentina, aged between 6 and 17 years old, with different socioeconomic backgrounds. The instrument used for data collection was an interview, in search for participants’ narratives about justice in their everyday life. In the responses of the interviewees three representations of justice could be distinguished: utilitarian, retributive and distributive. Approximately from 9-10 years old onward, these basic representations become intertwined with each other by a dialectical movement of integration and differentiation, which is an expression of a developmental process. It is concluded that the conceptualization process, within the ontogenesis of SR of justice, implies the construction of novelties under social and cognitive constraints that enable the construction of specific meanings about this social object an disable other possible meanings.